Effect of Bulk Acoustic Wave in Piezo Driven Nanomechanical Motion - Roy, S. K.; Hiebert, W. K. (Journal of Scientific Research, 2022)
Piezo actuation of mechanical resonators is widely adapted because of its simplicity and versatility. Piezo-driven atomic force microscopy cantilevers in air or liquid have a substantial drawback in that they produce spurious resonances that conceal the cantilever resonance peak. Bulk acoustic wave propagation via the piezo-shaker and device substrate causes these undesired peaks. Such restrictions of piezo actuation are rarely reported in nanomechanical resonant sensing. Because most NEMS (nanoelectromechanical systems) experiments are carried out at low pressure to achieve a higher quality factor ) and hence increased sensitivity, spurious resonances are frequently overlooked due to their insignificance. However, this piezo-driven issue may affect NEMS responses at higher pressures (lower Q) and must be addressed carefully. This study reveals spurious resonances from high vacuum to the atmosphere while investigating piezo-driven nanoscale doubly clamped beam responses. At all pressures, spurious peaks with a characteristic frequency span independent of air damping exist, and at higher pressures, they squeeze the mechanical peak. Such squeezing provides a larger derived from the driven phase responses by order of magnitude than the mechanical computed from the measured thermal noise spectra. Interestingly, the characteristic frequency span, not air damping, is revealed to dominate driven .